Analysis of Vulnerability Assessment Technique Implementation on Network Using OpenVas - Muhammad Muharrom; Afif Saktiansyah (Universitas Bumigora Mataram-Lombok, 2023)
Vulnerability Assessment is an important method for identifying and analyzing security vulnerabilities within a network system. This research aims to identify security vulnerabilities within the PT. Dutakom Wibawa Putra network using OpenVAS as a research tool. In the vulnerability analysis phase, OpenVAS is utilized to scan the PT. Dutakom Wibawa Putra network and identify existing vulnerabilities. Subsequently, an evaluation is conducted on the identified vulnerabilities, including risk assessment and necessary mitigation recommendations. The outcomes of this study provide a clear overview of the security vulnerabilities present in the PT. Dutakom Wibawa Putra network. This research using method analysis of vulnerability assessment technique implementation on network using OpenVas, several significant vulnerabilities that could impact the security of the network and systems have been identified. The findings of this analysis report can serve as a foundation for developing improved security strategies and implementing effective mitigation measures. In conclusion, this study successfully applies Vulnerability Assessment techniques to the PT. Dutakom Wibawa Putra network using OpenVAS. The identified vulnerability analysis results offer valuable insights into security weaknesses that need to be addressed. It is hoped that this research can serve as a reference for PT. Dutakom Wibawa Putra and similar organizations in enhancing their network security through the implementation of effective Vulnerability Assessment techniques.